THE IMAGES OF THE LOVER AND THE RIVAL IN SAKKOKI’S POETRY - Shakhnoza Rakhmanova (International Journal of Literature and Language Studies, 2026)
The article examines the ways in which the images of the lover (ʿāshiq) and the rival (raqīb) are represented and interpreted in Sakkoki’s ghazals. Through an analysis of selected poems, it explores the artistic functions, symbolic meanings, and ideological significance of these two central figures within the poet’s lyrical world. Particular attention is given to the lover as the embodiment of sincerity, devotion, and spiritual suffering, and to the rival as a force that obstructs union and intensifies the lover’s emotional trials.